Analgesic Efficacy of "Burst" and Tonic (500 Hz) Spinal Cord Stimulation Patterns: A Randomized Placebo‐Controlled Crossover Study. Issue 3 (29th November 2020) - Eldabe, Sam; Duarte, Rui; Gulve, Ashish; Williams, Heather; Garner, Fay; Brookes, Morag; Madzinga, Grace; Buchser, Eric; Batterham, Alan M.
Abstract: Objectives: The aim of this study was to compare the efficacy in reducing pain intensity in adult subjects suffering from chronic back and leg pain of burst (BST) and tonic sub‐threshold stimulation at 500 Hz (T500) vs. sham stimulation delivered by a spinal cord stimulation (SCS) device capable of automated postural adjustment of current intensity. Materials and Methods: A multicentre randomized double‐blind, three‐period, three‐treatment, crossover study was undertaken at two centers in the United Kingdom. Patients who had achieved stable pain relief with a conventional SCS capable of automated postural adjustment of current intensity were randomized to sequences of BST, T500, and sham SCS with treatment order balanced across the six possible sequences. A current leakage was programmed into the implantable pulse generator (IPG) in the sham period. The primary outcome was patient reported pain intensity using a visual analog scale (VAS). Results: Nineteen patients were enrolled and randomized. The mean reduction in pain with T500 was statistically significantly greater than that observed with either sham (25%; 95% CI, 8%–38%; p = 0.008) or BST (28%; 95% CI, 13%–41%; p = 0.002). There were no statistically significant differences in pain VAS for BST versus Sham (5%; 95% CI, −13% to 27%; p = 0.59). Exploratory sub‐group analyses by study site and sex were also conducted for the T500 vs. sham and BST versus sham comparisons. Conclusions: The findings suggest a superior outcome versus sham from T500 stimulation over BST stimulation and a practical equivalence between BST and sham in a group of subjects with leg and back pain habituated to tonic SCS and having achieved a stable status with stimulation.